Tuning Rules for Fractional Order PID Controllers for Industrial Processes: A Conceptual Framework - Isah, L. M.; Dan-Isa, A. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2022)
This paper presents a brief review of Fractional Order Proportional, Integral and Derivative (FOPID) controllers. The prominent tuning procedures are presented and a conceptual framework for a new design of efficient FOPID controller is presented. The presented framework is based on the concept of output feedback, where a threshold is applied on the output response before feeding its feedback to the comparator. The threshold output was compared with the reference to make a proper decision on when a new controller gain should be selected. This way, control effort will be minimized and the system can settle as fast as possible. This paper presents a brief study of Fractional Order Proportional, Integral and Derivative (FOPID) controllers with their prominent tuning procedures and an introduction to a conceptualize idea for a new tuning technique that can be adopted for efficient tuning this type of controllers... The presented framework is based on the concept of output feedback, where a threshold is applied on the output response before feeding its feedback to the comparator. The idea was to compare the applied threshold output with the reference so as to make a proper decision on when a new controller gain should be selected. The result would be a minimized control effort and thus making the system to settle as fast as possible.